Glucose Sensing in Saliva - Jacopo Giaretta; Riccardo Zulli; Theja Prabhakar; Ronil J. Rath; Sina Naficy; Sara Spilimbergo; Paul S. Weiss; Syamak Farajikhah; Fariba Dehghani (Advanced Sensor Research)
Abstract Glucose plays critical roles in many human body functions, above all as a source of energy. Abnormal levels of glucose are correlated to different diseases, importantly including diabetes. As such, quantification of glucose levels in body fluids is essential for health monitoring. Blood tests and, more recently, portable interstitial fluid tests, currently represent the benchmarks for glucose detection. Inconvenient invasive methods such as blood tests pose burdens on both patients and the healthcare system. In this review, noninvasive approaches to measure glucose levels in the human body are discussed, utilizing saliva as an alternative to conventional blood samples. Techniques explored and with the potential to enhance accuracy and their associated challenges are discussed.